The Roles of Nanomaterials in Conventional and Emerging Technologies for Heavy Metal Removal: A State-of-the-Art Review - Subramaniam, Mahesan Naidu (Nanomaterials (Basel), 2019)
Heavy metal (HM) pollution in waterways is a serious threat towards global water security, as high dosages of HM poisoning can significantly harm all living organisms. Researchers have developed promising methods to isolate, separate, or reduce these HMs from water bodies to overcome this. This includes techniques, such as adsorption, photocatalysis, and membrane removal. Nanomaterials play an integral role in all of these remediation techniques. Nanomaterials of different shapes have been atomically designed via various synthesis techniques, such as hydrothermal, wet chemical synthesis, and so on to develop unique nanomaterials with exceptional properties, including high surface area and porosity, modified surface charge, increment in active sites, enhanced photocatalytic efficiency, and improved HM removal selectivity. In this work, a comprehensive review on the role that nanomaterials play in removing HM from waterways. The unique characteristics of the nanomaterials, synthesis technique, and removal principles are presented. A detailed visualisation of HM removal performances and the mechanisms behind this improvement is also detailed. Finally, the future directions for the development of nanomaterials are highlighted.